Monetizing Hijab: Analysis on State’s National Interest on the Growing Hijab Fashion Trend in Indonesia - Witri Elvianti; Nanda Amedina Putri (Journal of Islamic World and Politics, 2019)
Hijab and its practices grow consistently as an iconic fashion of Muslim womenin Indonesia. This phenomenon yields scholarly commentaries pertaining tothe motivation of hijab’s massive production and Muslim women in veilingas well as the socioeconomic impact it carries with. However, the discussionon what sources of power underlie such a trend is still underrated. Therefore, this study aims at elucidating why now hijab receives greater support from the government under Joko Widodo’s administration that illuminates massive production and consumption on hijab domestically. The analyst came to argue that hijab consumption and production has become Indonesia’s national interest along with the mushrooming liberalization in its economy. Employing the qualitative research method to explain the source of power that makes hijab marketable in global and national market, the analyst also found that this trend is widely undermined by the implementation of neo-liberal economic policy that stresses the power of economic liberation of every individual while maintaining the state as the ultimate power of directing economic trajectory. Thus, the government of Indonesia seems to reconcile with the increasing domestic and global market demand on hijab. It is due to the state’s interest in establishing Indonesia as a global hijab centre by 2020.